2018
DOI: 10.1038/s41545-018-0012-z
|View full text |Cite
|
Sign up to set email alerts
|

Socio-environmental drivers of sustainable adoption of household water treatment in developing countries

Abstract: Household water treatment (HWT) can effectively reduce exposure to unsafe drinking water at home. Understanding the characteristics of target groups who successfully adopt HWT, such as perception about water quality and usefulness of HWT, income, or parental education, is essential for enhancing the adoption of HWT in developing countries. The objective of this study is to analyze the interactions between such socio-environmental characteristics, rather than a single characteristic, in order to explain the ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…The motivators for behavior change and thus, the nature of these interventions, would depend on the local social, cultural and environmental characteristics, such as water quality (whether water has visible coloration, odor, or poor taste), perceived health risk associated with water quality, education level of the population, etc. 3 , 54 59 . The influence of these characteristics on HWT adoption has been extensively studied in literature and this knowledge, in addition to field studies with user groups, could be leveraged to facilitate sustained adoption of xylem filters (see Supplementary Note 9 for factors that affect behavior change and sustained adoption of HWT and examples of behavior change interventions for xylem filters) 54 – 60 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The motivators for behavior change and thus, the nature of these interventions, would depend on the local social, cultural and environmental characteristics, such as water quality (whether water has visible coloration, odor, or poor taste), perceived health risk associated with water quality, education level of the population, etc. 3 , 54 59 . The influence of these characteristics on HWT adoption has been extensively studied in literature and this knowledge, in addition to field studies with user groups, could be leveraged to facilitate sustained adoption of xylem filters (see Supplementary Note 9 for factors that affect behavior change and sustained adoption of HWT and examples of behavior change interventions for xylem filters) 54 – 60 .…”
Section: Resultsmentioning
confidence: 99%
“…3 , 54 59 . The influence of these characteristics on HWT adoption has been extensively studied in literature and this knowledge, in addition to field studies with user groups, could be leveraged to facilitate sustained adoption of xylem filters (see Supplementary Note 9 for factors that affect behavior change and sustained adoption of HWT and examples of behavior change interventions for xylem filters) 54 – 60 .…”
Section: Resultsmentioning
confidence: 99%
“…We therefore recommend that local authorities should build community awareness about the seasonal nature of microbial risks and the need to ensure effective and consistent treatment of drinking water prior to consumption. At the household level, proven strategies for ensuring good quality of stored drinking water include promoting household water treatment among households most willing and able to adopt it [26]. Outside of the home, a promising intervention that reduces reliance on individual behavior change includes installation of passive inline chlorinators in piped distribution schemes [27].…”
Section: Water Quality Testingmentioning
confidence: 99%
“…According to the study in South Africa, public perception of drinking water safety is primarily related to organoleptic qualities rather than socio-economic or demographic characteristics (Wright et al 2012). Daniel et al (2018) indicated that the interactions between socio-environmental characteristics of households and behaviour determinants should be studied to determine the adoption of household water treatment in developing countries.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%